A multi-perspective lens on web assurance seals: contrasting vendors' intended and consumers' perceived effects - Julian Löbbers; Sebastian Lins; Theresa Kromat; Alexander Benlian; Ali Sunyaev (Electronic Commerce Research, 2020)
Web assurance seals are actions taken by e-commerce vendors to increase their trustworthiness and alleviate consumers' concerns. In their essence, web assurance seals are a product of negotiations, adoptions, and settlements among various groups of interests (e.g., seal authorities, vendors, consumers, or governmental institutions). However, previous research has hitherto used a unilateral research perspective when studying web assurance seals (i.e., either consumer- or vendor-centric), which has acted as a gridlock for web assurance seal literature development. Drawing on signaling theory, we use a ranking-type Delphi study with three distinct, yet mutually supportive expert panels (N0.167em=0.167em60) to compare vendors' intentions to acquire web assurance seals and perceived effects by consumers. Our results uncover a mismatch between consumers' perceptions and vendors' intentions of web assurance seals, unintended side effects as well as vendors targeting other stakeholders than consumers, ultimately providing starting points for research to move forward.
Keywords: 380; Web assurance seals; Delphi study; Signaling theory; e-commerce